Determining the Material and Physical Properties of Alloy La₀.₈₅Ce₀.₁₅Ni₅ Used in Hydrogen Storage - Jasminská, N.; Brestovič, T.; Lázár, M.; Saksl, K.; Šulova, K.; Čarnogurská, M.; Bednárová, L. (Проблемы прочности, 2017)
The article addresses the determination of the physical and material properties of the alloy La₀.₈₅Ce₀.₁₅Ni₅ with a crystalline structure. The properties of the microstructure of the alloy were determined using a scanning electron microscope. The chemical composition was evaluated by energy-dispersive X-ray spectroscopy. An X-ray diffractometer was used to determine the phase composition of the alloy. Next, the alloy sample was subjected to measurements of hardness, thermal conductivity and heat capacity. The storage capacity of hydrogen in the alloy was determined using the pressure concentration isotherms method of measuring. For comparison, the storage capacity was also measured in the amorphous structure of the alloy formed by the melt spinning method. Установлены физические свойства сплава La₀.₈₅Ce₀.₁₅Ni₅ с кристаллической структурой. Микроструктурные свойства сплава определяли с помощью сканирующего электронного микроскопа, химический состав методом энергодисперсионной рентгеновской спектроскопии. Для определения фазового состава использовали рентгеновский дифрактометр. Проводили измерения твердости, теплопроводности и теплоемкости образца сплава. Аккумулирующую способность сплава по водороду определяли с помощью изотерм концентрации и давления. В целях сравнения аккумулирующую емкость измеряли также в аморфной структуре сплава, полученной методом формования из расплава.